2020
DOI: 10.1371/journal.pone.0241930
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diabetes mellitus on postoperative outcomes in individuals with non-small-cell lung cancer: A retrospective cohort study

Abstract: Objectives Studies showing that individuals with non-small cell lung cancer (NSCLC) and diabetes mellitus (DM) have reported poor outcomes after pulmonary resection with varying results. Therefore, we investigated the clinical impact of preoperative DM on postoperative morbidity and survival in individuals with resectable NSCLC. Patients and methods Data of individuals who underwent pulmonary resection for NSCLC from 2000 to 2015 were extracted from the database of Kyoto University Hospital. The primary endp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
2
12
1
Order By: Relevance
“…We speculate that the ratio of good versus poor glycemic control is a critical factor in the analysis of survival. A recent retrospective study on postoperative NSCLC supported our result that the worst survival appeared in DM patients with a higher HbA1c ( 30 ). Accumulating data has deciphered the biological rationale underneath the association between HbA1c and outcome of cancer patients.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We speculate that the ratio of good versus poor glycemic control is a critical factor in the analysis of survival. A recent retrospective study on postoperative NSCLC supported our result that the worst survival appeared in DM patients with a higher HbA1c ( 30 ). Accumulating data has deciphered the biological rationale underneath the association between HbA1c and outcome of cancer patients.…”
Section: Discussionsupporting
confidence: 77%
“…Patients with coexisting lung cancer and DM is an unneglectable population and the prevalence of DM in NSCLC varied depending on ethnicity, population, staging, and histology. Approximately one out of four advanced NSCLC patients had preexisting DM in this study, which appears to be higher than previously reported prevalence of DM (11%-18.8%) in lung cancer ( 2 , 3 , 9 , 30 ). A similar phenomenon of an increased prevalence of DM in a higher tumor stage was observed in the breast and colorectal cancer ( 31 , 32 ).…”
Section: Discussioncontrasting
confidence: 76%
“…Thus, the prognostic value of DM or HbA1c levels for patients treated with ICIs needs to be further evaluated. Reports on DM status range from 4.59-18.87% in the published data (14)(15)(16)21). In the present study, 15.04% of the patients had a history of DM before treatment.…”
Section: Discussionmentioning
confidence: 43%
“…In the present study, we found Ogawa et al also evaluated the preoperative HbA1c levels of AC patients who underwent surgery and found that a HbA1c level ≥8% was associated with the worst 5-year OS, and the tumors were more likely to undergo distant metastasis in the follow-up period (20). Other studies have collected data from lung cancer patients with DM; however, results on the prognostic value of DM status have not been consistent in survival analyses (14)(15)(16)21). Further, research on ICI therapy is scarce.…”
Section: Discussionmentioning
confidence: 61%
“…Finally, it is important to discuss the role of comorbid diabetes where RAGE expression is increased (Kay et al, 2016) and its impact on cancer outcomes. In non-small cell lung cancer, patients with comorbid diabetes experience lower survival rates (Bi et al, 2020) and poorer outcomes following lung resection (Komatsu et al, 2020). These observations appear consistent across a variety of cancers.…”
Section: Discussionmentioning
confidence: 99%